HUBUNGAN PENGETAHUAN TENTANG COVID 19 DENGAN KEPATUHAN KELUARGA PASIEN DALAM PENGGUNAAN APD (MASKER) DI RUANG ISOLASI RUMAH SAKIT HUSADA UTAMA SURABAYA - Taurina, S; Kholid Fauzi, Ahmad; Rozi, Fahrur; Uswatun Sholikhah, Dwi (LPPM STIKES HUSADA JOMBANG, 2023)
Hospitals as complex health care facilities must provide health services that aim to improve the health of patients or clients and maintain the health of hospital visitors. Because the hospital is not only a place of treatment, but can also be a health service facility that can be a source of infection for others, especially the Covid 19 virus, the purpose of the study was to determine the relationship between knowledge about Covid 19 and the patient's family compliance in the use of PPE (masks). The design of this research is analytic Corelation with a cross sectional approach. The research population was the entire family of patients at Husada Utama Hospital Surabaya, the research sample was 30 respondents who were taken by Quota sampling. The results showed that most of the respondents had a sufficient level of knowledge, namely 17 respondents (56.7%) while the majority of respondents were 23 (76.7%) obedient. The analysis use of the Spearman Rank test obtained a p-value of 0.001 <0.05 with a correlation value (r) of 0.749 indicating a high correlation strength and it can be concluded that H1 is accepted, meaning that there is a relationship between the level of knowledge of the patient's family about Covid 19 and the level of compliance of the patient's family in the use PPE (Masks) at Husada Utama Hospital Surabaya. The level of knowledge and compliance is influenced by many factors. So that in its implementation at the research site it is impossible to predict the results obtained by the researcher. Even though every patient's family who enters the hospital, the officer in the isolation room always provides the first education regarding the importance of wearing a mask while waiting for a patient to prevent the transmission of the Covid 19 virus